2013
DOI: 10.3109/15412555.2012.727919
|View full text |Cite
|
Sign up to set email alerts
|

Growing Awareness of the Importance of Health Literacy in Individuals with COPD

Abstract: Good communication will impact clinical practice by assisting patients in understanding health information as well as medical recommendations. Health literacy is important for communication between healthcare professionals and patients with Chronic Obstructive Lung Disease (COPD). In this article we review the concepts, definitions and measurement tools used to evaluate health literacy and recommend ways in which this information may be integrated into clinical practice. Increased awareness of health literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 59 publications
0
20
0
6
Order By: Relevance
“…Yes somewhat/No it hasn't/It made things worse. 6 Mostly satisfi ed/A bit dissatisfi ed/Very dissatisfi ed vs. Very satisfi ed.…”
Section: Resultsmentioning
confidence: 99%
“…Yes somewhat/No it hasn't/It made things worse. 6 Mostly satisfi ed/A bit dissatisfi ed/Very dissatisfi ed vs. Very satisfi ed.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the modest improvements noted in some studies may be related to the patients' level of literacy. [21][22][23][24] Although our booklet used simple language, 53.3% of the patients in the intervention group had not completed high school and may have found the content difficult. Literacy carries a stigma and therefore patients may not have identified a lack of understanding of the material provided.…”
Section: Discussionmentioning
confidence: 99%
“…Literacy carries a stigma and therefore patients may not have identified a lack of understanding of the material provided. 22,23 Eighty-seven percent (n=13) of the patients reported that nothing was required to improve the program. Although the intervention group included a higher proportion of patients with a low level of education, the increase in BCKQ suggests that the intervention adequately targeted patients who may have had low health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Hem ölçek ile SOY ölçümü, hem de kendi beyanı ile SOY düzeyini değerlendirme, bizim çalışmamızı karşılaştırma yapabilmesi nedeniyle önemli kılmaktadır. Buna göre, hem REALM, hem NVS'ye göre bireylerin %50'sinden fazlasının SOY düzeyi yeterli düzeyde bulunmasına rağmen, sağlık kuruluşlarında kendilerine verilen kağıtları %6, 6 …”
Section: Bulgularunclassified